2022
DOI: 10.48550/arxiv.2203.04634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic bias on parameterized tests of general relativity due to neglect of orbital eccentricity

Abstract: Gravitational-wave observations provide a unique opportunity to test General Relativity (GR) in the strong-field and highly-dynamical regime of the theory. Parameterized tests of GR are one well-known approach for quantifying violations of GR. This approach constrains deviations in the coefficients of the post-Newtonian (PN) phasing formula, which describes the gravitational-wave phase evolution of a compact binary as it inspirals. Current bounds from this test using LIGO/Virgo observations assume that binarie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The parameterized test then attempts to constrain the size of those perturbations (with zero perturbation corresponding to GR). In [54] we found that the systematic bias on parameterized deviation coefficients become significant at e 0 ∼ 0.04 at 10 Hz in the LIGO band and at e 0 ∼ 0.005 at 10 Hz in the CE band.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…The parameterized test then attempts to constrain the size of those perturbations (with zero perturbation corresponding to GR). In [54] we found that the systematic bias on parameterized deviation coefficients become significant at e 0 ∼ 0.04 at 10 Hz in the LIGO band and at e 0 ∼ 0.005 at 10 Hz in the CE band.…”
Section: Introductionmentioning
confidence: 63%
“…(2.13) is the leading-order [i.e., O(e 2 0 )] eccentric correction to the inspiral stationary phase approximation (SPA) phasing [60] discussed earlier. See [49,54] for more details and applications of systematic errors arising from eccentric corrections. Note that the eccentric corrections ∆Ψ that induce systematic parameter errors in Eq.…”
Section: Waveform and Parameter Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The accurate computation of the gravitational waves (GW) from eccentric compact binary mergers has recently prompted a vibrant activity by the analytical and numerical relativity community [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A main goal of this programme is to provide GW templates for binaries on generic orbits to be used in the next scientific observational runs of the LIGO-Virgo-Kagra (LVK) collaboration [19][20][21] and in the future LISA observations [26][27][28].…”
Section: Introductionmentioning
confidence: 99%